Quality cost reduction in digital camera manufacturing process - Manowichian, Jantiwa; Kantanantha, Nantachai (Engineering and Applied Science Research, 2014)
This research aims to reduce the cost of quality from defects in a digital camera manufacturing process. The research is started from collecting the cost of quality data and studying the occurred defect types by using the Pareto diagram. Next, the defect types, chosen by the Pareto priority index, are analyzed to determine the main causes by applying the failure mode and effect analysis technique. These causes are then ordered according to the risk priority number and selected to determine the way to reduce the defects. In the manufacturing process improvement, the chi-square test and full factorial design of experiment are applied. After the improvement, the defects are reduced from 4.21 percent to 0.85 percent and the cost of quality is reduced from 1.27 million baht per month to three hundred thousand baht per month. In addition, the risk priority numbers are decreased 80 to 90 percent.